Penerapan Model Pembelajaran Kooperatif Tipe JIGSAW Untuk Meningkatkan Motivasi Belajar Siswa - Kadun, Satria Omega (P3M STT Kristus Alfa Omega, 2024)
Teaching in school requires a proper learning model to maximize student learning motivation. This study uses literature studies to analyze several studies related to the topic of speech, namely: cooperative learning, jigsaw learning model, and learning motivation. Cooperative learning is learning in a small, heterogeneous group to contribute in constructing concepts and solving problems with shared responsibilities and goals as well as positive interdependence while practicing interaction, communication, and socialization. Jigsaw learning model has heterogeneous origin groups to make students members share information with friends who discuss different topics within their home group. The result of this study shows that cooperative jigsaw learning affects student learning motivation.